Nanocomposites: Smart Albumin‐Biomineralized Nanocomposites for Multimodal Imaging and Photothermal Tumor Ablation (Adv. Mater. 26/2015). (6th July 2015) - Wang, Yong; Yang, Tao; Ke, Hengte; Zhu, Aijun; Wang, Yangyun; Wang, Junxin; Shen, Junkang; Liu, Gang; Chen, Chunying; Zhao, Yuliang; Chen, Huabing
<x xml:space="preserve">Abstract</x> A nanoplatform of cancer‐targeted nanocomposites is demonstrated by H. B. Chen and co‐workers on page 3874 through the assembly of gadolinium oxide nanocrystals with a protein scaffold in conjugation with near‐infrared cyanine dye, directed to trimodal near‐infrared fluorescence/photoacoustics/magnetic‐resonance imaging with complementary features, including ultrasensitivity, precise anatomical localization, and good spatial resolution, as well as smart photothermal efficacy with tumor ablation.